Metabolic rescue ameliorates mitochondrial encephalo‐cardiomyopathy in murine and human iPSC models of Leigh syndrome. Issue 7 (25th July 2022) - Yoon, Jin‐Young; Daneshgar, Nastaran; Chu, Yi; Chen, Biyi; Hefti, Marco; Vikram, Ajit; Irani, Kaikobad; Song, Long‐Sheng; Brenner, Charles; Abel, E. Dale; London, Barry; Dai, Dao‐Fu
Abstract: Background: Mice with deletion of complex I subunit Ndufs4 develop mitochondrial encephalomyopathy resembling Leigh syndrome (LS). The metabolic derangement and underlying mechanisms of cardio‐encephalomyopathy in LS remains incompletely understood. Methods: We performed echocardiography, electrophysiology, confocal microscopy, metabolic and molecular/morphometric analysis of the mice lacking Ndufs4. HEK293 cells, human iPS cells‐derived cardiomyocytes and neurons were used to determine the mechanistic role of mitochondrial complex I deficiency. Results: LS mice develop severe cardiac bradyarrhythmia and diastolic dysfunction. Human‐induced pluripotent stem cell‐derived cardiomyocytes (iPS‐CMs) with Ndufs4 deletion recapitulate LS cardiomyopathy. Mechanistically, we demonstrate a direct link between complex I deficiency, decreased intracellular (nicotinamide adenine dinucleotide) NAD + /NADH and bradyarrhythmia, mediated by hyperacetylation of the cardiac sodium channel NaV 1.5, particularly at K1479 site. Neuronal apoptosis in the cerebellar and midbrain regions in LS mice was associated with hyperacetylation of p53 and activation of microglia. Targeted metabolomics revealed increases in several amino acids and citric acid cycle intermediates, likely due to impairment of NAD + ‐dependent dehydrogenases, and a substantial decrease in reduced Glutathione (GSH). Metabolic rescue by nicotinamide riboside (NR) supplementation increased intracellular NAD + / NADH, restored metabolic derangement, reversed protein hyperacetylation through NAD + ‐dependent Sirtuin deacetylase, and ameliorated cardiomyopathic phenotypes, concomitant with improvement of NaV 1.5 current and SERCA2a function measured by Ca2 + ‐transients. NR also attenuated neuronal apoptosis and microglial activation in the LS brain and human iPS‐derived neurons with Ndufs4 deletion. Conclusions: Our study reveals direct mechanistic explanations of the observed cardiac bradyarrhythmia, diastolic dysfunction and neuronal apoptosis in mouse and human induced pluripotent stem cells (iPSC) models of LS. Abstract : Leigh syndrome (LS) is a severe mitochondrial encephalomyopathy that may involve heart. Its metabolic derangement is characterized by NAD + deficiency and impairment of several NAD + ‐dependent metabolic enzymes and Sirtuins. Nicotinamide Riboside restores Sirt1 function, reverses hyperacetylation of several crucial proteins, including Nav1.5 and SERCA2 in cardiomyocytes, and p53 in the brain, leading to amelioration of bradycardia, neuronal loss and encephalopathy.